2008
DOI: 10.1136/ard.2008.095836
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance imaging in systemic sclerosis: a cross-sectional observational study of 52 patients

Abstract: Objectives:To assess the prevalence and patterns of cardiac abnormalities as detected by cardiac magnetic resonance imaging (MRI) in systemic sclerosis (SSc).Methods:Fifty-two consecutive patients with SSc underwent cardiac MRI to determine morphological, functional, perfusion at rest and delayed enhancement abnormalities.Results:At least one abnormality on cardiac MRI was observed in 39/52 patients (75%). Increased myocardial signal intensity in T2 was observed in 6 patients (12%), thinning of left ventricle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
151
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(171 citation statements)
references
References 27 publications
13
151
3
4
Order By: Relevance
“…Age-related changes in cardiac responses to high pressure loads (20) may explain some of the apparent differences in RV contractility between IPAH and SSc-PAH, but direct myocardial involvement from SSc due to microvascular disease or fibrosis may also be a contributing factor. A high prevalence of early RV dysfunction has been observed in patients with SSc without PAH as determined by endomyocardial biopsy (23), magnetic resonance imaging (24)(25)(26)(27), and tissue-Doppler echocardiography (28)(29)(30)(31)(32), although the presence of PH induced by exercise was evidenced in one of the studies (29).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in cardiac responses to high pressure loads (20) may explain some of the apparent differences in RV contractility between IPAH and SSc-PAH, but direct myocardial involvement from SSc due to microvascular disease or fibrosis may also be a contributing factor. A high prevalence of early RV dysfunction has been observed in patients with SSc without PAH as determined by endomyocardial biopsy (23), magnetic resonance imaging (24)(25)(26)(27), and tissue-Doppler echocardiography (28)(29)(30)(31)(32), although the presence of PH induced by exercise was evidenced in one of the studies (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in cardiac imaging, such as magnetic resonance imaging (MRI), have shown that a majority of patients have at least one abnormality on cardiac MRI [33]. We have previously shown that one third of patients have diastolic dysfunction and around 21% have myocardial delayed-contrast enhancement suggestive of myocardial fibrosis [33].…”
Section: Cardiac Involvementmentioning
confidence: 99%
“…Bardzo pomocne jest oznaczanie stężenia NT-proBNP, ponieważ stwierdzono korelację między jego wartościami a PAP, oraz wykonanie testu 6-minutowego marszu [49]. Obecnie coraz częściej rekomenduje się badanie serca metodą rezonansu magnetycznego (magnetic resonance imaging -MRI) [50].…”
Section: Gastrointestinal Diseaseunclassified
“…Highly beneficial examinations also include NTproBNP testing, because of a correlation between NT-proBNP and the PAP value, and 6-minute walking test [49]. Cardiac examination by magnetic resonance imaging (MRI) is increasingly recommended nowadays [50]. wykonania obliczenia należy skorzystać z kalkulatora dostępnego na stronie http://detect-pah.com/ [42,43].…”
Section: Cardiac Diseasementioning
confidence: 99%